Innovations in Tribology and Surface Engineering: A Systematic Literature Review in Mechanical Engineering - Abdul Aziz (Science and Applied Journal (SIAP), 2024)
This study presents a systematic literature review of innovations in the field of tribology and surface engineering, with a focus on the development of superhydrophobic coatings in mechanical engineering. The study background includes an understanding of the importance of tribology and surface engineering in improving material performance, while the research objective is to evaluate recent advances in the application of nanotechnology in the development of superhydrophobic coatings. The research method involves collecting articles from reputable international databases, with the use of relevant keywords to search for relevant articles. The results of the discussion include an understanding of the basic concepts of tribology, the application of nanotechnology in surface engineering, the characteristics of super hydrophobic coatings, and the application of nanotechnology in the development of superhydrophobic coatings. The implication of this research is that a deep understanding of tribology, surface engineering, and nanotechnology can help in developing more efficient and sustainable engineering solutions. This study makes an important contribution to the understanding of the potential of nanotechnology in improving the tribological performance of materials and developing more efficient and sustainable mechanical engineering solutions.